The efficacy and safety of direct oral anticoagulants vs traditional anticoagulants in cirrhosis. (15th January 2017) - Hum, Justine; Shatzel, Joseph J.; Jou, Janice H.; Deloughery, Thomas G.
Abstract: Introduction: The coagulopathy of cirrhosis is complex, placing patients at risk for both bleeding and thrombosis. Direct oral anticoagulants (DOACs) have equivalent or superior efficacy and safety as compared to vitamin K antagonists (VKAs); however, their efficacy and safety in liver cirrhosis has not been studied. To better define this, we evaluated outcomes of patients with cirrhosis prescribed DOACs compared to other anticoagulants at our center. Methods: Retrospective cohort study of patients with cirrhosis prescribed therapeutic anticoagulation over a 3‐year period for thrombosis or prevention of stroke in patients with atrial fibrillation. The primary outcomes of interest were bleeding events and recurrent thrombosis or stroke. Results: During the study period, 27 patients with cirrhosis were prescribed a DOAC and 18 were prescribed VKA or low molecular weight heparin (LMWH). Both groups had similar total bleeding events (8 DOAC vs 10 other, P =.12). There were significantly less major bleeding episodes in the DOAC group (1 [4%] vs 5 [28%], P =.03). Recurrent thrombosis occurred in one patient receiving a DOAC (4%) and one patient (6%) receiving other anticoagulation ( P =1.0). Conclusions: Direct oral anticoagulant use in patients with cirrhosis may be as safe as traditional anticoagulants. Patients with cirrhosis at our center prescribed DOACs had less major bleeding events, while maintaining efficacy at preventing stroke or thrombosis.